The Right to Internet: Characterization of Public Policies Related to Internet Access and Connectivity as Social Policy in the Aburrá Valley by Territorial Entities - Roncancio Bedoya, Andres F.; Calle, Santiago López; Taborda, Santiago Agudelo; Carrillo Benítez, Cristian C. (Law, State and Telecommunications Review, 2024)
[Purpose] The paper analyzes how municipalities, as decentralized entities, can develop public policies on Internet access as part of their social function, taking as a reference the territorial entities that make up the metropolitan area of the Aburrá Valley (Antioquia - Colombia). [Methodology] Research methods such as deduction, content analysis and comparative analysis, together with other documentary techniques, were used to approach the study from a qualitative and comparative law approach. [Findings] The study examines public policies on Internet access in the Aburrá Valley from 2008 to 2023, highlighting Medellín's leadership in this area. Although some municipalities have more modest advances and the lack of a specific regulatory framework, as in Caldas, limits the formulation of effective policies. In addition, the proactive response to the pandemic and the recognition of the digital divide as a social problem reflect a continued commitment to digital inclusion in the region.